Manajemen Sekolah pada Kurikulum Merdeka Terkait Project Penguatan Profil Pelajar Pancasila (P5) - Maryanah Maryanah; Suyono Suyono; Radeni Sukma Indra Dewi (Departement of Mathematics Education, 2024)
The Merdeka Curriculum, launched in 2022, focuses on strengthening Pancasila values through the Pancasila Student Profile, including character dimensions like faith, independence, cooperation, and creativity. One key program, the Project to Strengthen the Pancasila Student Profile (P5), integrates project-based learning with the surrounding environment. P5 aims to develop students' character and skills through intramural, co-curricular, and extracurricular activities. This study uses a literature review to analyze the management of P5 in schools, based on data from Google Scholar and the Publish or Perish app. The Merdeka Curriculum requires careful planning, including learning goals, assessment, and technology integration, to support character development and Pancasila values. P5 combines both intramural and extracurricular learning, providing students opportunities for investigation, problem-solving, and producing outcomes that reflect Pancasila values in everyday life.